2010
DOI: 10.1016/j.radonc.2009.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effectiveness of radiotherapy with photons, protons and carbon-ions for non-small cell lung cancer: A meta-analysis

Abstract: Survival rates for particle therapy were higher than those for CRT, but similar to SBRT in stage I inoperable NSCLC. Particle therapy may be more beneficial in stage III NSCLC, especially in reducing adverse events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
157
0
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 292 publications
(167 citation statements)
references
References 71 publications
4
157
0
6
Order By: Relevance
“…carbon ions in treating NSCLC [Grutters et al, 2010]. They found similar 5-year survival rates for SBRT, protons and carbon-ions (around 40%).…”
Section: Grutters Et Al Have Performed a Meta-analysis On Comparisonmentioning
confidence: 85%
See 1 more Smart Citation
“…carbon ions in treating NSCLC [Grutters et al, 2010]. They found similar 5-year survival rates for SBRT, protons and carbon-ions (around 40%).…”
Section: Grutters Et Al Have Performed a Meta-analysis On Comparisonmentioning
confidence: 85%
“…A stereotactic body radiation treatment (SBRT) shows good results for treating NSCLC [Baumann et al, 2009, Fakiris et al, 2009, Grutters et al, 2010, Greco et al, 2011. Furthermore, several studies have shown that SBRT can be used in the setting of limited metastatic disease [Rusthoven et al, 2009, Villaruz et al, 2012, Salama et al, 2012, Iyengar et al, 2014.…”
Section: Introductionmentioning
confidence: 99%
“…A meta-analysis by Grutters et al showed that the OS at 5 years for SBRT and conventional radiotherapy were 42.1% and 19.5%, respectively [4]. The introduction of SBRT in the treatment of elderly NSCLC patients is associated with an improvement in OS, as shown by Palma et al.…”
Section: Introductionmentioning
confidence: 93%
“…Stereotactic body radiation therapy (SBRT) for peripheral stage I non-small cell lung cancers (NSCLC) is recognized as a standard treatment for medically inoperable patients [1][2][3][4][5][6]. Nagata et al reported that the overall survival (OS) for stage IA and IB NSCLC patients at 3 years were 83% and 72%, respectively [1].…”
Section: Introductionmentioning
confidence: 99%
“…However, these studies were small and most were retrospective. Therefore, a meta-analysis was performed to compare the efficacy of chemoradiotherapy, photon SBRT, PBT and carbon ion therapy for stage I inoperable NSCLC [23]. Carbon ion therapy is one of the particle radiotherapies, as well as PBT, but carbon ion beams are categorized as high LET radiation.…”
Section: Clinical Results Of Pbt For Early Stage Non-small-cell Lung mentioning
confidence: 99%